The Influence of Entrepreneurship Orientation and Market Orientation on the Performance of Small and Medium Enterprises Mediated by Competitive Advantage - Satria Tirtayasa (Enrichment : Journal of Management, 2022)
This study aims to determine the effect of entrepreneurial orientation and market orientation on the performance of small and medium enterprises mediated by competitive advantage in the construction of a welding workshop at the Medan City Court. This study uses an associative approach. The population of this study was all Small and Medium Industries located on Jalan Medan Kota Court. The sampling technique used in this study is saturated, amounting to 100 respondents. Data collection techniques through questionnaires or questionnaires that have been tested for validity and reliability. The data analysis used in this research is the Structural Equation Model (SEM) method with the alternative method of Partial Least Square (PLS). The results showed that: (1) the influence of entrepreneurship orientation on the performance of SMEs is positive and significant (2) the effect of market orientation on the performance of SMEs is positive and significant. (3) the influence of entrepreneurial orientation on competitive advantage is positive and significant. (4) the influence of market orientation on competitive advantage is positive and significant. (5) the effect of competitive advantage on the performance of SMEs is positive and significant (6) competitive advantage plays a role in mediating entrepreneurial orientation on the performance of MSMEs (7) Competitive advantage plays a role in mediating the effect of market orientation on the performance of MSMEs.